Double‐Layer Structure Photoanode with TiO2 Nanotubes and Nanoparticles for Dye‐Sensitized Solar Cells. Issue 2 (20th November 2012) - Cao, Liqiang; Wu, Congcong; Hu, Qin; Jin, Tetsuro; Chi, Bo; Pu, Jian; Jian, Li
Abstract : Here, we report a novel double‐layer structure photoanode with TiO2 nanotube (TNT) layer and TiO2 nanoparticle (TP) layer via a two‐step method of electrochemical anodization and screen printing for dye‐sensitized solar cells (DSSCs). The results indicate that DSSCs with this double‐layer structure have significant advantages of large surface area, long electron lifetime, superior electron recombination restraint characteristics, and high light scattering. The layer thickness of nanotubes and nanoparticles is also investigated and finally an optimized double‐layer structure with excellent performance is prepared. With such a double‐layer structure photoanode, DSSC with a relative high conversion efficiency of 6.43% and a short‐circuit photocurrent density of 16.40 mA·cm −2 is obtained.